The Influence of Corporate Social Responsibility (CSR) and Brand Loyalty With Variables Mediating Brand Experience and Trust - Azizah Sani Wijaya; Ratna Roostika (Publikasi Indonesia, 2024)
This study aims to test and analyse the effect of corporate social responsibility (CSR) on cosmetics consumer loyalty with brand experience and brand trust as mediating variables. The methodology in this study uses a quantitative approach with purposive sampling technique. The criteria for respondents in this study are cosmetics consumers with an age range of > 17 years. The number of valid respondents in this study was 205. Data processing in this study is using the PLS-SEM method and SPSS. This study uses the variables of corporate social responsibility (CSR) influence, brand experience, brand trust and brand loyalty. The results of this study indicate that the influence of corporate social responsibility (CSR) has a positive effect on brand experience. Corporate social responsibility (CSR) has an effect on brand trust. Corporate social responsibility (CSR) affects brand loyalty. Brand experience affects brand trust. Brand experience affects brand loyalty and brand trust affects brand loyalty.